Die erste Suchreise des FFS "Anton Dohrn" im Jahre 1965 (85.Reise) - Reinsch, H.H. (1965)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010